Prevalence of work-related burnout and associated factors among police officers in central Gondar zone, Northwest Ethiopia, 2023 - Bezie, Anmut Endalkachew; Getachew Yenealem, Dawit; Asega Belay, Azanaw; Bitew Abie, Alebachew; Abebaw, Tadiwos; Melaku, Christian; Mamaye, Yimer; Hailu Tesfaye, Amensisa (Frontiers in Public Health, 2024)
Introduction: Work-related burnout (WRB) is a state of physical and psychological fatigue and exhaustion resulting from chronic workplace stress related to work. The police workforce is a vulnerable occupation, which affects the service delivery by police workers. But there is little evidence about the prevalence and associated factors of work-related burnout among police officers in Ethiopia. Therefore, this study aims to assess the prevalence and associated factors of work-related burnout among police officers in central Gondar zone, Ethiopia, 2023.Methods: An institution-based cross-sectional study was conducted from April to May, 2023. A sample of 633 police officers was recruited through multistage random sampling techniques. A standardised, self-administered Copenhagen burnout inventory was used to measure work-related burnout. The data were entered into EpiData V. 4.6 and analysed using SPSS V. 26. Bivariable (p<0.2) and multivariable logistic regression analysis was done to examine the association between work-related burnout and associated factors. The statistical significance was established in multivariable logistic regression at a p-value of <0.05 with a 95% confidence interval.Results: In this study, the response rate was 96.05% (n = 608). The overall prevalence of WRB in the last six months was 45.7% [95% CI (41.75, 49.6 9)]. Female [AOR: 4.298; 95% CI (3.274, 8.573)], high job demand [AOR: 1.561, 95% CI (1.045, 3.332)]. High organizational police stress [AOR: 2.231; 95% CI (1.076, 4.624)], moderate and high operational police stress [(AOR: 2.349; 95% CI (1.309, 4.216)], [AOR: 4.881; 95% CI (2.385, 9.992)], job dissatisfaction [AOR: 1.910, 95% CI (1.054, 3.461)] and, sleeping troubles [AOR: 1.522; 95% CI (1.032, 2.244)], were risk factors significantly associated with work-related burnout.This study revealed that the prevalence of work-related burnout was high among police officers. Sex, job demand, job satisfaction, operational police stress, organizational police stress, and sleeping troubles were found to be significant factors associated with the occurrence of work-related burnout. To reduce the condition, it is recommended to take measures to cope with high job demands, improve stress management skills, give priority to job satisfaction and policewomen, and ensure adequate and quality sleep.